Literatur Review: Pencemaran Merkuri di Perairan Indonesia - Syifa Thifal Umaira; Syavira Azzahra; Nadiya Mufidah; Firdus Firdus; Muhammad Nasir; Alia Rizki; Fauziah Fauziah (Universitas Syiah Kuala, 2024)
Mercury (Hg) belongs to a group of heavy metals that can pollute the environment. Pollution caused by mercury in the environment will cause bioaccumulation in aquatic biota, which then impacts human health. Mercury, especially in the form of methyl mercury, can be harmful to the central nervous system, causing sensory impairment and even permanent paralysis. Mercury pollution comes from various mining activities, industry, agriculture, household waste, and mercury mining itself. Accumulation of mercury in excess of quality standards can be dangerous and cause many negative impacts. This study examines pollution caused by mercury in Indonesian waters. The results showed that the objects most polluted by mercury are water, sediment, and aquatic biota. The highest percentage of pollution is found in rivers (39%), and the lowest in lakes and reservoirs (3%).